Does Weak Governance Cause Weak Stock Returns? An Examination of Firm Operating Performance and Investors' Expectations - CORE, JOHN E.; GUAY, WAYNE R.; RUSTICUS, TJOMME O. (Journal of Finance, 2006)
ABSTRACT We investigate Gompers, Ishii, and Metrick's (2003) finding that firms with weak shareholder rights exhibit significant stock market underperformance. If the relation between poor governance and poor returns is causal, we expect that the market is negatively surprised by the poor operating performance of weak governance firms. We find that firms with weak shareholder rights exhibit significant operating underperformance. However, analysts' forecast errors and earnings announcement returns show no evidence that this underperformance surprises the market. Our results are robust to controls for takeover activity. Overall, our results do not support the hypothesis that weak governance causes poor stock returns.